2022
DOI: 10.3390/ijms23074022
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of the Branched Chain Amino Acids (BCAAs) Catabolism-Regulating Enzymes, Branched-Chain Aminotransferase (BCAT) and Branched-Chain α-Keto Acid Dehydrogenase (BCKD), in Human Pathophysiology

Abstract: Branched chain amino acids (BCAAs), leucine, isoleucine and valine, are essential amino acids widely studied for their crucial role in the regulation of protein synthesis mainly through the activation of the mTOR signaling pathway and their emerging recognition as players in the regulation of various physiological and metabolic processes, such as glucose homeostasis. BCAA supplementation is primarily used as a beneficial nutritional intervention in chronic liver and kidney disease as well as in muscle wasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 122 publications
0
75
0
Order By: Relevance
“…BCAAs metabolize into acetyl coenzyme A and propionyl coenzyme A, which are substrates for lipid synthesis. Excess carbon produced by catabolism of BCAA may lead to an increase in the rate of adipogenesis ( 29 ). Research has reported that fat accumulation in the liver was reduced after BCAAs supplementation in a rat experiment.…”
Section: Microbiota and Branched-chain Amino Acid-associated Metaboli...mentioning
confidence: 99%
“…BCAAs metabolize into acetyl coenzyme A and propionyl coenzyme A, which are substrates for lipid synthesis. Excess carbon produced by catabolism of BCAA may lead to an increase in the rate of adipogenesis ( 29 ). Research has reported that fat accumulation in the liver was reduced after BCAAs supplementation in a rat experiment.…”
Section: Microbiota and Branched-chain Amino Acid-associated Metaboli...mentioning
confidence: 99%
“…Patients with a deficiency in the enzyme pyruvate dehydrogenase (PDH) have shown a significantly larger increase in plasma alanine levels compared to those with mitochondrial disease [20]. Mitochondrial disease criteria (MDC) scoring systems, such as the modified Walker criteria [21], define abnormal metabolic studies, such as high alanine levels, as a minor criterion of mitochondrial dysfunction. According to the Nijmegan protocol, a plasma alanine level of >450 mM in patients is used to help determine the likelihood of mitochondrial dysfunction [21].…”
Section: Amino Acidsmentioning
confidence: 99%
“…Mitochondrial disease criteria (MDC) scoring systems, such as the modified Walker criteria [21], define abnormal metabolic studies, such as high alanine levels, as a minor criterion of mitochondrial dysfunction. According to the Nijmegan protocol, a plasma alanine level of >450 mM in patients is used to help determine the likelihood of mitochondrial dysfunction [21]. However, an increase in serum alanine concentrations has been identified in other conditions, such as sepsis, hyperinsulinism and chronic thiamine deficiency [22].…”
Section: Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations